Exploiting Cross-Layer Vulnerabilities: Off-Path Attacks on the TCP/IP Protocol Suite. - Feng, Xuewei; Li, Qi; Sun, Kun; Xu, Ke; Wu, Jianping (Communications of the ACM, 2025)
The article looks at cyber security, focusing on the TCP/IP Internet protocol. It analyzes various vulnerabilities in TCP/IP use, including some related to the forgery of Internet Control Message Protocol (ICMP) error messages. Possible solutions are discussed.